Monitoring adverse events of low-dose glucocorticoid therapy: EULAR recommendations for clinical trials and daily practice. Issue 11 (6th August 2010) - van der Goes, M C; Jacobs, J W G; Boers, M; Andrews, T; Blom-Bakkers, M A M; Buttgereit, F; Caeyers, N; Cutolo, M; Da Silva, J A P; Guillevin, L; Kirwan, J R; Rovensky, J; et al.
Abstract : Objective: To develop recommendations on monitoring for adverse events (AEs) of low-dose glucocorticoid (GC) therapy (≤7.5 mg prednisone or equivalent daily) in clinical trials and daily practice. Methods: Literature was searched for articles containing information on incidence and monitoring of GC-related AEs using PubMed, EMBASE and Cochrane databases. Second, the authors searched for broad accepted guidelines on the monitoring of certain AEs (eg, WHO guidelines on screening for diabetes). Available data were summarised and discussed among experts (rheumatologists and patients) of the EULAR Task Force to decide which potential AEs should be monitored, how and at which interval. Results: Data on monitoring proved to be scarce; most articles were focused on therapeutic effects of GCs, not on occurrence and monitoring of AEs. Most recommendations had to be based on consensus. Those for clinical trials aimed at getting insights into incidence, prevalence and clinical relevance of AEs to create a comprehensive and valid AE-profile of GC therapy. The set of AEs to monitor is therefore more extensive, and often consists of assessments at baseline and at end of trials. Recommendations for daily practice are meant to protect patients from real dangers, which can be prevented or treated. Standard care monitoring needs NOT be extended for patients on low-dose GC therapy, except for osteoporosis (follow national guidelines), and baseline assessments of ankle edema, fasting blood glucose and risk factors for glaucoma. Conclusion: Given the incompleteness of literature data, consensus-based recommendations on monitoring for GC-related AEs were created, separately for daily practice and clinical trials.